Large-eddy simulation of flow over a cylinder with $Re_{D}$ from $3.9× 10^{3}$ to $8.5× 10^{5}$: a skin-friction perspective. (5th May 2017) - Cheng, W.; Pullin, D. I.; Samtaney, R.; Zhang, W.; Gao, W.
Abstract : We present wall-resolved large-eddy simulations (LES) of flow over a smooth-wall circular cylinder up to $Re_{D}=8.5× 10^{5}$, where $Re_{D}$ is Reynolds number based on the cylinder diameter $D$ and the free-stream speed $U_{∞ }$ . The stretched-vortex subgrid-scale (SGS) model is used in the entire simulation domain. For the sub-critical regime, six cases are implemented with $3.9× 10^{3}\leqslant Re_{D}\leqslant 10^{5}$ . Results are compared with experimental data for both the wall-pressure-coefficient distribution on the cylinder surface, which dominates the drag coefficient, and the skin-friction coefficient, which clearly correlates with the separation behaviour. In the super-critical regime, LES for three values of $Re_{D}$ are carried out at different resolutions. The drag-crisis phenomenon is well captured. For lower resolution, numerical discretization fluctuations are sufficient to stimulate transition, while for higher resolution, an applied boundary-layer perturbation is found to be necessary to stimulate transition. Large-eddy simulation results at $Re_{D}=8.5× 10^{5}$, with a mesh of $8192× 1024× 256$, agree well with the classic experimental measurements of Achenbach ( J. Fluid Mech., vol. 34, 1968, pp. 625–639) especially for the skin-friction coefficient, where a spike is produced by the laminar–turbulent transition on the top of a prior separation bubble. We document the properties of the attached-flow boundary layer on the cylinder surface as these vary with $Re_{D}$ . Within the separated portion of the flow, mean-flow separation–reattachment bubbles are observed at some values of $Re_{D}$, with separation characteristics that are consistent with experimental observations. Time sequences of instantaneous surface portraits of vector skin-friction trajectory fields indicate that the unsteady counterpart of a mean-flow separation–reattachment bubble corresponds to the formation of local flow-reattachment cells, visible as coherent bundles of diverging surface streamlines.